The influence of introducing artificial intelligence (AI) on the future of employees' jobs in Saudi governmental sector: Applied study to the Ministry of Justice in Asir Region - Al- Taledy, Mufreh Jaber Mesfer (Journal of Economic, Administrative and Legal Sciences, 2021)
The present research aimed to identify the influence of introducing artificial intelligence (AI) on the future of employees' jobs at the Ministry of Justice in Asir region. The descriptive analytical approach has been adopted and the research tool has been in the questionnaire. The research population represents all employees at the Ministry of Justice in Asir region whose number is (2720) employees. A random sample of (88) employees has been chosen. The research concluded several conclusions, the most important of which is that the reality of artificial intelligence (AI) at the Ministry of Justice in Asir region was high, and it became clear that the extent of the change in the quantity and quality of jobs after introducing artificial intelligence (AI) at the Ministry of Justice in Asir region was high. There are no statistically significant differences in employees' viewpoints at the Ministry of Justice in Asir region about the influence of introducing artificial intelligence (AI) on the future of their jobs according to (academic qualification - age - years of experience). The research proposed a set of recommendations, the most important of which is to develop and enhance the concept of artificial intelligence (AI) in achieving the daily tasks at the Ministry of Justice by following it constantly and the need to emphasize the application of artificial intelligence (AI) in all government sectors because of its effective impact on the performance of employees in general and on providing job opportunities for new innovations, and the need to pay attention to creating new job opportunities by attracting experts in the field of artificial intelligence (AI) to follow up its developments in order to improve the work environment at the Ministry of Justice.
Keywords: artificial intelligence; the future of jobs